THE EFFECT OF BRAND AWARENESS AND PRODUCT QUALITY ON CONSUMER LOYALTY TO JNC SNACK FOOD PRODUCTS COOKIES IN BANDUNG CITY - Define Haifa Rahmaeni; Ine Aprianti; Pupi Indriati Zaelani; Hersusetiyati Hersusetiyati (PT. Altin Riset Publishing, 2026)
JNCCookies faces challenges in maintaining revenue stability outside of seasonal periods. The preliminary survey results indicate that consumer brand awareness of JNC Cookies is relatively low and that the product quality has not fully met consumer satisfaction, thereby affecting consumer loyalty.This study aims to analyze the influence of brand awareness and product quality on consumer loyalty using a qualitative method quantified through a descriptive and verificative approach involving 100 respondents. The novelty of this research lies in its focus on the relationship between brand awareness and product quality toward consumer loyalty at JNC Cookies, which has not been extensively studied specifically within the handmade cookie industry in Bandung City.The findings reveal that both brand awareness and product quality have a effect on consumer loyalty, both partially and simultaneously. These results emphasize that both factors play an essential role in building long term consumer loyalty.Based on these findings, JNC Cookies is recommended to strengthen its marketing strategies through more intensive promotions, building a strong brand identity, and creating unique product characteristics that differentiate it from competitors in order to foster stronger and more sustainable consumer loyalty.